Chronology of Organochlorine Pesticides (OCPs) releases and interactions with sediment characterisitcs in the Eure River, France - Thomas Gardes; Florence Portet-Koltalo; Maxime Debret; Yoann Copard (PANGAEA, 2021)
We reconstruct the chronology of organochlorine pesticides (OCPs) releases and study the role of sediment characteristics (e.g organic matter) in the interpretation of this chronology. For that, sediment cores MAR16-02 and MAR15-01 were collected downstream of the Eure River watershed, the main tributary of the Seine estuary (France). The analysis of particulate OCPs in the MAR16-02 sediment core was performed using microwave-assisted extraction, with toluene:acetone mixture for extraction. Following the microwave-assisted extraction, a gas chromatograph (7890B, Agilent, US) coupled to a mass spectrometer (MS; 7000C) was used to measure the concentrations. Organic matter parameters from MAR15-01 sediment core was measured by Rock-Eval 6.